Extended producer responsibility for fossil fuels* At a time of high fossil fuel prices and rents, we show that applying the principle of extended producer responsibility to fossil fuels, implemented through a combination of geological storage and nature-based solutions, could deconflict energy security and climate policy at an affordable cost. (1st January 2023) - Jenkins, Stuart; Kuijper, Margriet; Helferty, Hugh; Girardin, Cécile; Allen, Myles
Abstract: Energy policy faces a triple challenge: increasing resilience and guaranteeing the security of supply of both fossil and non-fossil energy, minimising the impact on consumer energy prices, and retaining consistency with Paris Agreement climate goals. High prices and producer rents, however, also present an opportunity: to open a conversation about applying the principle of extended producer responsibility (EPR) to fossil fuels. We demonstrate that this could deconflict energy security and climate policy at an affordable cost by stopping fossil fuels from causing further global warming. Implementing EPR through a combination of geological CO2 storage and nature-based solutions can deliver net zero at comparable or lower costs than conventional scenarios driven with a global carbon price and subject to constraints on CO2 storage deployment. It would also mean that the principal beneficiary of high fossil fuel prices, the fossil fuel industry itself, plays its part in addressing the climate challenge while reducing the risk of asset stranding.